ANALISIS HASIL KALIBRASI ALAT PHOTOTHERAPY MERK GEA MEDICAL TYPE XHZ-90 - Yeni Pertiwi; Nur Hadziqoh; M Andriza Mustofa (Komunikasi Fisika Indonesia, 2022)
Babies born prematurely always increase every year. For this reason, it is necessary to take proper care so that the baby remains in good health. One of the treatments for premature babies is phototherapy to reduce bilirubin levels in the baby's body. In order for the phototherapy process to run as expected, of course the phototherapy equipment used in the treatment must be of good quality and quality. For this reason, quality assurance and phototherapy equipment need to be carried out through a calibration process. In this study, calibration of the GEA medical type XHZ-90 phototherapy tool was carried out. Calibration is carried out by following the standard reference work method from the Ministry of Health in 2018. Calibration is carried out by checking the physical and function of the equipment which gains a weight of 10%, electrical safety inspection of the appliance with a weight gain of 36%, and measuring the performance of the instrument, namely spectral irradiance with a weight gain of 50%. . So that the total weight gain can be 96% and it can be concluded that this tool is functioning properly and within the tolerance limits of use. The uncertainty value in the measurement of spectral irradiance takes into account the sources of uncertainty types A and B. The combined uncertainty calculation from several sources for the measurement of spectral irradiance is 1.116. This value has met the uncertainty tolerance limit value of ≥ 4.